2008
DOI: 10.1016/j.cytogfr.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumors with LIGHT to generate metastasis-clearing immunity

Abstract: Metastastic diseases cause the majority of morbidity and mortality of cancer patients. Established tumors form both physical and immunological barriers to limit immune detection and destruction. Current immunotherapy of vaccination and adoptive transfer shows limited effect at least in part due to the existing barriers in the tumors and depending on the knowledge of tumor antigens. Tumor necrosis factor superfamily member 14 (TNFSF14) LIGHT interacts with stromal cells, dendritic cells, NK cells, naïve and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 97 publications
(124 reference statements)
2
46
0
Order By: Relevance
“…Indeed, earlier studies indicated that LIGHT can promote dendritic cell expansion and maturation, especially when in cooperation with CD40L (29,30). Second, LIGHT can induce the expression of chemokines by stromal cells to attract T cells migrating into the tumors (31). Third, LIGHT can promote Teff expansion and differentiation, even in a Treg-enriched environment, as we have shown in this paper.…”
Section: Discussionsupporting
confidence: 51%
“…Indeed, earlier studies indicated that LIGHT can promote dendritic cell expansion and maturation, especially when in cooperation with CD40L (29,30). Second, LIGHT can induce the expression of chemokines by stromal cells to attract T cells migrating into the tumors (31). Third, LIGHT can promote Teff expansion and differentiation, even in a Treg-enriched environment, as we have shown in this paper.…”
Section: Discussionsupporting
confidence: 51%
“…Constitutive expression of LIGHT can enhance the extravasation and homing of naive T cells (19,20). Moreover, recent data further confirmed the role of LIGHT in priming potent antitumor immunity (17,(21)(22)(23)(24)(25). For instance, we have showed that forced expression of LIGHT in the tumor could induce a massive infiltration of naive T cells into tumor tissues.…”
Section: Introductionmentioning
confidence: 51%
“…Our previous data have shown that LIGHT could prime potent antitumor immunity (22,24,25). To determine whether expression of LIGHT on MSCs still possesses potent antitumor immunity, we first carried out the experiments with nude mice.…”
Section: Immune Activation By Msc-l Contributes To Tumor Regressionmentioning
confidence: 99%
“…The relative location of CTLs to TLS may be important for CTLs receiving help from T helper cells for generation of an effective and durable antitumor immune response. Interestingly, it has been reported that LIGHT, a TNF superfamily member and a ligand for the lymphotoxin b receptor, facilitates the generation of TLS (39,40) and recruits na€ ve T cells into the tumor (41). Expression of LIGHT in tumors has been shown to enhance chemokine secretion within the tumor, favoring the infiltration and expansion of functional CD8 þ T cells (42).…”
Section: Anatomical Locationmentioning
confidence: 99%